Copolymer based multifunctional conducting polymer film for fluorescence sensing of glucose. (29th May 2018) - Ayranci, Rukiye; Kirbay, Fatma Ozturk; Demirkol, Dilek Odaci; Ak, Metin; Timur, Suna
Abstract: A simple, rapid and effective fluorescence sensing platform has been fabricated using a fluorescent conducting polymer surface. For this purpose, a rhodamine based electroactive monomer (RDC) and a functional group containing monomer (SNS) have been copolymerized to develop a conducting polymer based sensor platform having a fluorescence and enzyme-binding surface on ITO electrode. The proposed fluorescence sensing mechanism for detection of glucose is related to the consumption of dissolved oxygen at the double layer of the electrode which is fluorescence quenching agent by glucose-GOx reaction. Concentration of glucose was investigated quantitatively from 0.05 to 1 mM via fluorescence signal measurement. This novel approach could be adapted for the production of various rapid and effective fluorescence sensing platforms for glucose.